The Relationship Between Marital Burnout and Psychological Capital with Psychological Hardiness in Conflicted Couples - Moutabi, Sirous; Fattahi, Nabi (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to examine the extent to which marital burnout and psychological capital predict psychological hardiness in couples experiencing marital conflict.Methods and Materials: The research design was descriptive–correlational with a predictive approach. The statistical population comprised couples with marital conflicts who visited the Armaghan Bahar Counseling Center, the Niyan Goal-Oriented Growth and Development Center, and the Savalan Center in Karaj during the first six months of 2024. Using the Tabachnick and Fidell sample size formula N ≥ 50 + 8M, 160 participants were selected through non-probability purposive sampling. Data were collected using validated instruments, including the Marital Conflicts Questionnaire (Sanaei et al., 2008), the Marital Burnout Scale (Pines, 1996), the Psychological Capital Questionnaire (Luthans, 2007), and the Psychological Hardiness Scale (Kobasa et al., 1982). After obtaining informed consent, participants completed the paper-based questionnaires under researcher supervision. Data analysis was performed using SPSS version 24 with Pearson’s correlation and multiple regression analysis.Findings: Results indicated that marital burnout had a significant and negative predictive relationship with psychological hardiness (t = -5.601, β = -0.399, p < .001), while psychological capital had a significant and positive predictive relationship with psychological hardiness (t = 4.619, β = 0.329, p < .001). Together, marital burnout and psychological capital explained 39% of the variance in psychological hardiness (R² = .399).Conclusion: Marital burnout significantly undermines psychological hardiness, while psychological capital acts as a protective resource that enhances resilience and adaptability in conflicted couples.